A Critical Thinking Capability Analysis of Student Worksheets in A Collaborative Learning Environment - Qomariyah, Siti; Rosyidah, Ummi; Ayuwanti, Irma (Universitas PGRI Madiun, 2023)
The ability to think critically in mathematics is one of the cognitive abilities that students require in order to learn problem-solving techniques and arrive at logical conclusions, particularly while dealing with advances in the twenty-first century. One method is to use live worksheet-assisted cooperative learning. The goal of this study was to assess students' critical thinking abilities when using LKS-assisted cooperative learning. This study employs a descriptive research design with a qualitative methodology. Thirty eighth-grade students participated in the study. Lesson plans, observation sheets, assessments, and interviews are examples of research instruments. Data collection methods include observation, exams, and interviews. Students' post-test results showed that 17 students scored 72.36% in the category of high critical thinking ability, three categories of students scored 9.67%, and students in the category of low critical thinking ability scored 6.67%. Adopting cooperative learning settings with LKPD support can also aid enhance student engagement throughout mathematics instruction, with an average of 82.1% activity.